Rapid Detection of Candida tropicalis in Clinical Samples From Different Sources Using RPA-LFS - Wang, Lei; Xu, Aiguo; Zhou, Ping; Zhao, Mengdi; Xu, Chenglai; Wang, Yan; Wang, Kun; Wang, Fang; Miao, Yongchang; Zhao, Weiguo; Gao, Xuzhu (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Candida tropicalis, a common pseudofilamentous yeast, belongs to the order Cryptococcaceae and family Cryptococcaceae. At present, the commonly used clinical methods for the identification of this organism are traditional fungal culture, CTB staining, and color development. Polymerase chain reaction (PCR) and real-time quantitative PCR (qPCR) are also used to identify this fungus. Since the course of C. tropicalis infection progresses rapidly, there is an urgent need for rapid, sensitive, real-time field assays to meet the needs of clinical diagnosis. Recombinase polymerase amplification (RPA) combined with lateral flow strip (LFS) can rapidly amplify and visualize target genes within 20 min, and by pre-processing samples from different sources, the entire process can be controlled within 30 min. In this study, RPA-LFS was used to amplify the internal transcribed spacer-2 (ITS2) gene of C. tropicalis, and primer-probe design was optimized by introducing base mismatches to obtain a specific and sensitive primer-probe combination for clinical sample detection. LFS assay for 24 common clinical pathogens was performed, sensitivity and specificity of the detection system was determined, reaction temperature and time were optimized, and 191 actual clinical samples collected from different sources were tested to evaluate the detection performance of the established RPA-LFS system to provide a reliable molecular diagnostic method for the detection of C. tropicalis, and to meet the clinical need for rapid, sensitive, real-time, and portable field testing.